An Appraisal of Igbo Traditional Justice System in Contemporary Society - Elizabeth Okon John; Philip Onyedikachi Obasi (Pinisi Journal of Social Science, 2025)
Before the advent of western civilisation, traditional Africans' conduct and behaviour were regulated by ethical principles and customary laws. The elders in traditional African societies had always settled private disputes, problems, and criminal complaints. These ethical principles and customary laws were meant to maintain social order and stability in the society. Judgment and punishment were meted out based on merit and the crimes committed respectively. While some punishments were meted out by the gods, others were distributed according to the laws of the land. However, in contemporary times, the modern legal system built on a western worldview has been adopted as the accepted paradigm for justice. Though these customary laws partially exist and are sometimes applied, their relevance in contemporary society is subject to debate. This work aims at evaluating the practice and relevance of the Igbo traditional justice system in contemporary society. The work brings to the fore the challenges of traditional Igbo justice systems. The work adopts both the sociological and phenomenological approaches in its investigation. It submits that with the advent of the modern legal system, the level of injustice in urban and rural settlements has increased, as justice is perverted and denied by legal practitioners.